2018
DOI: 10.1002/1873-3468.13218
|View full text |Cite
|
Sign up to set email alerts
|

The trans isomer of Tau peptide is prone to aggregate, and the WW domain of Pin1 drastically decreases its aggregation

Abstract: In Alzheimer's, the disease-related protein Tau is hyperphosphorylated and aggregates into neurofibrillary tangles (NFT). The cis isomer of the phosphorylated Thr231-Pro232 has been proposed as a precursor of aggregation ('Cistauosis'), but this aggregation scheme is not yet completely accepted. Here, we synthesized peptides comprising a phosphorylated region including Thr231-Pro232 and an aggregation-core region R1 to investigate isomer-specific-aggregation of Tau. The phosphorylated peptide formed amyloid-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…One study suggested that the trans isomer of tau peptide is prone to aggregate, and the WW domain of Pin1 drastically decreases its aggregation. 530 It could be possible that both trans-tau and cis-tau are able to aggregate, depends in the environment in the experimental conditions to change their energy landscape. Accelerated MD were used to explore the conformational landscape of the tau segment containing the phosphorylated-Thr( 231)-Pro(232) motif.…”
Section: Impact Of Phosphorylation and Other Ptm On Tau Aggregationmentioning
confidence: 99%
See 1 more Smart Citation
“…One study suggested that the trans isomer of tau peptide is prone to aggregate, and the WW domain of Pin1 drastically decreases its aggregation. 530 It could be possible that both trans-tau and cis-tau are able to aggregate, depends in the environment in the experimental conditions to change their energy landscape. Accelerated MD were used to explore the conformational landscape of the tau segment containing the phosphorylated-Thr( 231)-Pro(232) motif.…”
Section: Impact Of Phosphorylation and Other Ptm On Tau Aggregationmentioning
confidence: 99%
“…Other conflicting results were also observed in the proneness of aggregation. One study suggested that the trans isomer of tau peptide is prone to aggregate, and the WW domain of Pin1 drastically decreases its aggregation . It could be possible that both trans-tau and cis-tau are able to aggregate, depends in the environment in the experimental conditions to change their energy landscape.…”
Section: Extensive Simulations On Monomers and Small Oligomersmentioning
confidence: 99%
“…It is possible that other factors or modifications promote tau aggregation. The ratio of cis/trans isoforms may affect fibrillarization and in vitro data suggest that in particular the trans isomer of a tau peptide is prone to aggregate (125). Isomerization is regulated by the protein Pin1, which binds to the PRR of tau.…”
Section: Pathological Changes Of the Interactions Of The Microtubule Binding Regionmentioning
confidence: 99%
“…The structure of full-length Pin1 was determined by X-ray crystallography, after introducing five mutations G44E/ G45N/K46L/N47Y/G48F in the linker region between the two domains, and expressing and purifying this protein [12]. The full-length C113A mutant was obtained by substituting a hydrogen for the sulfur Sγ of C113.…”
Section: Simulationsmentioning
confidence: 99%
“…1). In additional experiments, the functions of this mutant were shown to be equivalent to those of wild-type Pin1 [12]. Therefore, we dealt with this mutant protein as the wild-type protein in this study, and then obtained the C113A mutant by substituting a hydrogen for the sulfur Sγ of C113.…”
Section: Initial Structuresmentioning
confidence: 99%